The Influence of Bureaucratic Simplification and Organizational Culture on Employee Performance with Motivation as an Intervening Variable in the East Java Province DPRD Secretariat Environment - Rochani, Oktavia Siti; Hermawan, Sigit; Sriyono, Sriyono (Budapest International Research and Critics University, 2024)
This research aims to analyze the influence of Bureaucratic simplification on Work Motivation, analyze the influence of Bureaucratic Simplification on Employee Performance, analyze the influence of Organizational Culture on Work Motivation, analyze the influence of Organizational Culture on Employee Performance, analyze the influence of Motivation on Employee Performance, analyze the influence of Organizational Culture on Employee Performance through work motivation, and analyzing the influence of Bureaucratic Simplification on Employee Performance through work motivation within the East Java Province DPRD Secretariat. The sample size in this research involved 100 employees. The analysis technique uses SEM-PLS analysis. The results of the analysis show that simplifying bureaucracy has an effect on work motivation. Bureaucratic simplification affects employee performance. Organizational culture influences work motivation. Organizational culture influences employee performance. Motivation influences employee performance. Organizational culture influences employee performance through work motivation. Bureaucratic simplification affects employee performance through work motivation within the East Java Province DPRD Secretariat.